Emprego da ultra-sonografia nas lesões bucomaxilofaciais - Sother, Márcia Duarte (2007)
Ultrasonography is an ultrasound-based diagnostic imaging method based on the clinical application of ultrasound. It is a complementary image-based examination method, non-invasive, painless and with not actually known deleterious effect. It is a technique able to detect, define and evaluate the internal aspects of the oral-maxillofacial complex, thus becoming an advantageous method in imagenology based diagnosis. This work had as objectives evaluate the application of ultrasonography in the diagnostic of intraosseous lesions and/or swellings of the oral-maxillofacial complex and correlate ultrasonography-based diagnosis with radiographic and histopathological evaluation results. This was a prospective study with 12 selected patients. All the patients underwent radiographic, ultrasonographic and histopathological evaluation of biopsy samples from the affected area. The results showed correlation among radiographic and ultrasonographic findings in all histopathologically confirmed intraosseous cysts. All soft tissues lesions exhibited an ultrasonographic image. Ultrasonography is able to register images of both intraosseous lesions and soft tissues. However we believe more investigation is needed about recommendation of this complementary exam for intraosseous lesions evaluation.